IMPLEMENTASI SISTEM KEUANGAN DESA DALAM PENGELOLAAN ALOKASI DANA DESA DI DESA SUKADIRI KECAMATAN SUKADIRI KABUPATEN TANGERANG - Windy Annisa; Yulia Eka Wulandari; Gun Gun Gumilar; Indra Aditya (Universitas Dian Nuswantoro, 2023)
Sistem Keuangan Desa (Siskeudes) is an application that aims to make village financial management transparent and accountable. This application was created with the aim of facilitating the process of checking village financial management, one of which is supervision regarding the use of Village Fund Allocation (ADD). This study intends to further identify the implementation of the Village Financial System on the management of Village Fund Allocation in Sukadiri Village, Sukadiri District, Tangerang Regency using the policy implementation theory proposed by George Edward III (1980) consisting of 4 (four) indicators, namely communication, resources, disposition, and bureaucratic structure. The research method used is descriptive qualitative with data collection techniques, namely observation, interviews and documentation. The subjects in this study include the Village Head and Village Secretary. The results showed that the implementation of Siskeudes carried out by the Government of Sukadiri Village, Sukadiri District, Tangerang Regency was quite optimal. However, when viewed based on indicators of resources and bureaucratic structure, there are still several problems due to the lack of ability of village apparatus to operate the Siskeudes application so that it requires assistance from Siskeudes Operators who are non-structural personnel and the absence of SOPs for the implementation of Siskeudes owned by the Sukadiri Village Government, causing village financial reporting into Siskeudes to often experience delays.